PERANAN PENDIDIKAN KEPENDUDUKAN DAN LINKUNGAN llll)UP DALAM MENGATASI MASALAH KEPENDUDUKAN DI INDONESIA - Subardhy Subardhy (Jurnal Cakrawala Pendidikan, 2000)
The population problelns in Indonesia basicallyselns fonn the high birth rate which causes the highspeed of population growth. Unfortunatly, this can notmeet their life-need supply : food, cloth, houses,facil ities for education, health, and emp)oynlent. Suchcondition bringsJow quality of ITIOst Indonesianpopulation. In edition, the effort by tranmigration toiimprove prosperity in some exten has not beensuccesful. This phenomenonl of population must beanticipated by carriying out an activity which changesthis behavvior. The behaviorual changes cannothappen without educational activity. Therefore, PKLHas an educational program to provide childern withunderstanding , awarness, atitude, and rationalresponible behavior, andto understand the relationshipbetween population and environment in all of hUlnanaspects.The children who have PKLH educationare-expected to be aware that birth is not Inerely a Inatterof but it can be pp]atned. Therefore, thefanlily size is not destiny, it can be also behuman are also tobe aware that a small is reasonable andarationalto the of social and theirownHife. Childern with PKLH are to behave their that preserveschildern with PKLH will becolnewho attitude towardsOlal1norm and appy their The acceptenc